Teaching sexuality education in the HIV and AIDS education curriculum : the voices of high school guidance and counselling teachers - Gudyanga, Ephias; Gudyanga, Anna; Wadesango, Newman (African Perspectives of Research in Teaching & Learning (APORTAL), 2022)
The study focused on teaching sexuality education in the HIV and AIDS education curriculum in high schools. In spite of the importance of HIV and AIDS education in preventing HIV infections, Guidance and Counseling (G&C) teachers are not engaging optimally with the current curriculum, and hence, they are not serving the needs of the learners in the context of the HIV and AIDS pandemic. Situated within a qualitative research design, and informed by a critical paradigm, we used participatory visual methodology, with drawing and focus group discussion as methods for data generation. Eight female G&C urban secondary school teachers, purposively selected, comprised the sample of participants. Thematic analysis was used to analyse the data. The findings revealed that the G&C teachers have an understanding of the curriculum and made their voices heard on how it is to be taught. Even though they were enthusiastic to teach sexuality education - in the age of HIV and AIDS they became aware that their system of education did not appear to optimally support their work. They understood that the participatory visual methodology could enable them to teach their current G&C curriculum. They, furthermore, could reflect on themselves, the context in which they taught their sexuality education, work and learn from each other. In this way, their agency seemed to have been enabled to address the challenges and consider how they could teach sexuality education in their schools. Drawing on Cultural Historical Activity Theory, we conclude that the G&C teachers could be enabled to teach sexuality education if the three Activity Systems, namely the G&C teachers, the school system, and the community, work together as one Activity System, engaging with each other in a generative way focused on the same outcome.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 6 (2) (2022)
Keywords: Cultural Historical Activity Theory; Guidance; Counseling; HIV and AIDS; Participatory visual methodology; Sexuality education; Critical theory; AIDS (Disease); HIV (Viruses); Sex instruction; Counseling in secondary education; Educational counseling; Teachers